Ù†ÙˆØ§Ù‚Ø¶ Ø§Ù„ÙˆØ¶ÙˆØ¡ Ø¹Ù†Ø¯ Ø§Ù„Ø´Ø§ÙØ¹ÙŠØ© ÙˆØ§Ù„ØÙ†Ø§Ø¨Ù„Ø© (Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ø±Ù†Ø©) - Muhammad Yusram; Saifullah Bin Anshor; Sinatra, Sinatra (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
Ablution is a great form of taharah so Sharia makes it a legal condition of prayer. The four schools have agreed on most problems related to ablution, such as its pillars, its obligations, its circumcision and its nullifiers, but they are also different in some ways. This study aims to find out the opinions of Shafi'i and Hanbali schools about ablution and things which invalidate it, as well as strong opinions of both. The scientific methods used to achieve results are inductive-deductive and comparison methods. The results showed that the things which invalidate it according to the Shafi'i school there are four things and according to the Hanbali school there are seven. Then there is the difference of opinion between the two schools in this matter on four points, namely: the feces coming out of the body as thing can invalidate the ablution, sleeping while sitting, touching women and eating camel meat. This research is expected to contribute in the field of comparative jurisprudence of schools, especially in the problem of nullifiers of ablution according to Shafi'i and Hanbali schools, and increasing knowledge in this matter.